O α-bisabolol protege camundongos da perda neuronal e déficits cognitivos em modelo animal de doença de Alzheimer esporádica induzido por estreptozotocina - Bezerra, Jéssica Rabelo (2019)
Alzheimer's disease (AD) is a progressive neurodegenerative disease characterized by the formation of amyloid and intracellular neurofibrillary plaques in cortical areas, leading to progressive memory loss and cognitive impairment, being a more common form of dementia. Intracerebroventricular (icv) injections of streptozotocin (STZ) has been used as an experimental model of sporadic AD in rodents because they cause impairment in insulin signaling, oxidative stress, neuroinflammation and neurogenesis dysfunctions, which result in cognitive and are characteristic of sporadic AD (SAD). The main purpose of this study was to study the effects of α-bisabolol, a sesquiterpene, which has anti-inflammatory, anti-oxidant and anti-apoptotic activity already described, on neuronal damage and cognitive deficits in mice submitted to the experimental model of ADS induced by STZ. Male Swiss mice (25-35 g) received injections of STZ (3 mg/kg, icv) bilaterally on day 1 and 3 of the experiment. Treatment with α-bisabolol (50, 100 and 200 mg/kg, orally) or vehicle (Tween 3% + saline) was performed for 16 days, starting 2 h after the second induction procedure. Blood was collected for glucose analysis, before and after induction of SAD. The results showed that there was no significant change in blood glucose levels. Treatment with α-bisabolol significantly improved working memory, aversive memory, recognition memory and spatial memory, and don’t change the locomotors activity. The α-bisabolol was not able to decrease nitrite concentration in the prefrontal cortex and hippocampus but was able to decrease the MDA increase concentration in the prefrontal cortex decreasing by 55% at the dose of 100 mg/kg and in 53.24% at the dose of 200mg/kg. The α-bisabolol (100 and 200 mg/kg) also increased cell viability and increased synaptophysin expression, 57,21 % and 68,32 % respectively, in the hippocampus. These results suggest that the neuroprotective activity of α-bisabolol is related to anti-oxidant activity and synaptic protection, highlighting its therapeutic or adjuvant potential for the treatment of SAD.